Surface modification of work material using Powder Metallurgey (P/M) compacted electrodes during Electric Discharge Machining (EDM) - Khan, Ahsan Ali (s.n, 2012)
Powder metallurgy (P/M) electrodes are additional innovation in the operation of electrical discharge machining (EDM). In this process the EDM cutting tool is produced from powders by the P/M compaction method. This research project aims to develop the P/M compacted electrodes from powders and used them to modify the surfaces of the work materials. Two types of composite P/M electrodes were developed from copper (Cu), cobalt (Co), chromium (Cr) and tantalum carbide (TaC) powders. These are Co-Cr and Cu-TaC composite electrodes. Their properties have been examined, and this led to the establishment of their suitability for EDM. They were used in electrical discharge machining of mild steel and titanium alloy (Ti-6Al-4V) materials. The EDM process outputs of material removal rate (MRR), tool wear rate (TWR) and electrode wear ratio (EWR) were used to evaluate the electrodes’ performance. Their suitability in EDM was thus established. The compacting pressure and composition were also found to influence their EDM performance in addition to the machining parameters. During the EDM, migration occurred from the electrode materials on to the work material surfaces. Analysis showed that Cr and Co were found on the surface of the mild steel after machining. Similarly, Cu and TaC were also found on the EDMed Ti-6Al-4V surface. This confirmed the electrodes’ ability to alloy work material during EDM. This alloying capability was used to increase the surface hardness of the mild steel by the Co-Cr electrode to about 85.30 HRB from 70.37 HRB. The Cu-TaC electrode was also used to improve the micro-hardness of the Ti-6Al-4V to 552.6 Hv. Further work is recommended on extension of this technique to improve the wear characteristics of the Ti-6Al-4V alloy with these electrodes.